An exploration of female early adolescent self-presentation and social comparisons, when engaging with social networking sites - Thompson, Emily Beth (2021)
Background The use of social networking sites (SNS), including Instagram and Snapchat, is an integral aspect of adolescent life (Throuvala et al., 2019). Existing research has explored the possible impact of using SNS, which is described as a ‘double-edged sword’ (Keles et al., 2020) due to its benefits and potential risks for adolescents. However, a significant proportion of research concerns a sample of older adolescents, this is despite findings that suggest children as young as eight years are accessing SNS every day (Children’s Commissioner, 2018). Alongside being frequent, devoted users of SNS (Shankleman et al., 2021) adolescence is also a formative developmental period for identity (Erikson, 1968). One’s identity is socially embedded (Davis, 2011) and individuals gain an insight into their performance through comparing themselves to others, which can be facilitated by SNS (Vogel et al., 2014). Therefore, it is necessary to further explore the development of self and social comparisons made on SNS, due to possible associations between SNS and this aspect of development. Furthermore, research utilising an early adolescent sample is required, to acknowledge the increased use of SNS, within this demographic.